Anti-hepatitis C virus core IgM antibodies correlate with hepatitis C recurrence and its severity in liver transplant patients. Issue 5 (1st November 2000) - Bizollon, T; Ahmed, S N Si; Guichard, S; Chevallier, P; Adham, M; Ducerf, C; Baulieux, J; Trepo, C
Abstract : BACKGROUND: The significance of immunoglobulin (Ig) M antibody to hepatitis C virus (HCV) core antigen was studied in 60 patients with HCV infection after orthotopic liver transplantation (OLT) diagnosed by polymerase chain reaction. METHODS: Patients were followed up for a mean of 28 months after transplantation. Sera collected three months before transplantation, and one and 12 months after transplantation were analysed for anti-HCV core IgM (HCV-IgM EIA 2.0 assay). After OLT protocol biopsies, procedures were performed routinely every six months. Semiquantitative histopathological assessment of allograft hepatitis was performed using Knodell's score. The results were correlated with clinical features, liver histology findings, and virological features, such as genotype and viraemic levels assessed by a branched DNA assay. RESULTS: One year after liver transplantation, 29/60 (48%) patients had chronic hepatitis on graft biopsy. The presence of anti-HCV core IgM one month (p=0.004) and 12 months (p=0.003) after OLT was positively correlated with recurrence of chronic hepatitis. The positive predictive value of anti-HCV core IgM detected one month after transplantation was 0.88. A significant relationship was observed between severity of graft disease and presence of anti-HCV core IgM 12 months after transplantation. The mean Knodell score was 8.9 in anti-HCV core IgM positive patients compared with 3.6 in those who were anti-HCV core IgM negative (p=0.001). The presence of IgM anti-HCV did not correlate with serum HCV RNA level or HCV genotype. CONCLUSION: We confirm that the presence of anti-HCV core IgM after OLT is a marker of HCV induced graft damage. The recurrence and severity of HCV hepatitis in patients undergoing OLT for HCV cirrhosis is related to the presence of anti-HCV core IgM after liver transplantation. These findings have diagnostic relevance and confirm that measurement of IgM anti-HCV core may help to better monitor the treatment of HCV recurrence after transplantation.